Índice de mensuração da economia criativa: aplicação do IDPEC em Pernambuco. - Souza, Jadiael Alexandre de (2022)
The “Creative Economy” is an evolving concept based on operational methods that potentially create growth and economical development. In this sense, this study has the purpose to measure the development potencial of the Creative Economy in Pernambuco, divided in three big regions: Zona da Mata, Agreste e Sertão. The standard to choose the localities was defined by the city wich has the biggest Gross Domestic Product in each region: Recife, Caruaru e Petrolina, repectively. The metodology used was based on the Development Potencial of the Creative Economy Index, created and apllied at the Capital Cities of the states and of the Federal District, by the Creative Economy, Development and Territory Laboratory, and by the Creative Cities Laboratory from ESPM-Rio, in three stages: (i) theorical revision in onder of comprehension about the concepts of the Creative Economy and the Index previously constructed and apllied to the comprehension of the dynamism related to the creative economy in our Country; (ii) Index selection to the analysis of the capital Recife reality and the countryside cities, Caruaru e Petrolina, divided in three dimensions (talent, attractiveness and conectivity; cultural ambience and creative entrepreunership), (iii) IDPEC’s calculation based on the allocation of same and different weights to the three mentioned dimensions. This study proposes a research guides by the following problem: How to measure the creative economy development potencial at the countryside cities in Brazil? The results obtained from the apllication of this Index will be relevant for the increment process of the methodological tools of creative economy measurement. The reasearch’s final results proves that the IDPEC is satisfactorily apllied in big cities, but in smaller cities its apllication can be harmed for not attending all the evaluation standards required in the three dimensions.